Pesquisa de empreendimentos e perfil dos empreendedores do centro comercial de Nova Cruz (RN) - Ananias, Matheus Silva (Universidade Federal Rural do Semi-Árido, 2019)
In the past few years, entrepreneurship has been a widely discussed subject in Brazil and across the world since the global economic crisis drove people to seek alternative sources of income. Noticing that the capitalist system in which the Economy is based on demands an increasingly competitive market setting, driving the products and services to become increasingly innovative. Undertaking survey and entrepreneurs profiles of Nova Cruz’s commercial center sets a wide-ranging goal of checking what is the town’s most common entrepreneurs profile, considering how the city’s economic setting influences such area of investment. To check a more specific way and to comprehend where the entrepreneurship is most likely to appear, we consider Company’s age, its owner’s age, its technology, method of use, already existing inside the market apps or individuals to attend their most common specific needs. At last, we seek to comprehend which factor is most likely to motivate the citizens into investing in this sector, whether the influence of courses, conversation among friends or heritage, for example. The importance of this job is based on the need of tracing an entrepreneurship profile in the city of Nova Cruz, besides analyzing its contribution to the state of Rio Grande do Norte, searching for the reasons why one seeks to invest. At the end of questionnaire (the ground of our academic research), we noticed that male individuals are prevailing within the city’s overall business and that the lack of incentives and information has led to that scenario, and that the absence of Industry and employment consequently drove the population to look for entrepreneurship to grow as human beings.
Monografia
Keywords: Empreendedor; Empreendedorismo; Nova Cruz - RN; Entrepreneur; Entrepreneurship; Nova Cruz – RN; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA